PHARMACEUTICAL LEGISLATION IN RUSSIA IN XVIII-XIX CENTURIES: THE FIRST RUSSIAN PHARMACOPOEIA, APOTHECARY STATUTES - Yu. I. Zelikson (Разработка и регистрация лекарственных средств, 2019)
The article gives an overview of the Russian pharmaceutical legislation in XVIII-XIX centuries and describes the first Russian departmental and government pharmacopoeia (1756, 1778, 1798). There is analyses the first Apothecary statue (1789) and the second Apothecary statue (1857). It is got experts from Apothecary Statues that reflecting the requirements of the time to the qualification, morals, responsibility of the pharmacist to the manufacturing and dispensing drugs.